Learning from the Cultural Legacy: Traditional Learning Strategy of Basandi Syara’ and Syara’ Basandi Kitabullah in the Ulu Ambek Dance - Ridho, Muhammad; Daryusti; Efi, Agusti; Agustina (Indonesian Research Journal in Education |IRJE|, 2025)
This research analyzes Ulu Ambek dance’s presentation and explores the adat’s symbolic meaning: "basandi syara’, syara’ basandi kitabullah." The study employs a qualitative approach with a descriptive method. The data is collected through literature review, observation, interviews, and documentation. The findings indicate that the Ulu Ambek dance symbolizes various social and cultural values, such as intergenerational relationships and respect for elders. The dance movements include sambah, which reflects obedience and the relationship between humans and the creator. The dance features two movement patterns: malalu (attack) and ambek (defense). The five main movements in Ulu Ambek are Ambek Sampiang, Ambek Cincin, Ambek Gewang Baju, Ambek Deta, Ambek Urek Tunggang. Additional movements present today serve to embellish the dance. There is no physical contact between dancers, distinguishing it from silek.